Utilization of Staphylococcal Immune Evasion Protein Sbi as a Novel Vaccine Adjuvant - Yang, Yi; Back, Catherine R.; Gräwert, Melissa A.; Wahid, Ayla A.; Denton, Harriet; Kildani, Rebecca; Paulin, Joshua; Wörner, Kristin; Kaiser, Wolgang; Svergun, Dmitri I.; Sartbaeva, Asel; Watts, Andrew G.; et al. (Frontiers in Immunology, 2019)
Co-ligation of the B cell antigen receptor with complement receptor 2 on B-cells via a C3d-opsonised antigen complex significantly lowers the threshold required for B cell activation. Consequently, fusions of antigens with C3d polymers have shown great potential in vaccine design. However, these linear arrays of C3d multimers do not mimic the natural opsonisation of antigens with C3d. Here we investigate the potential of using the unique complement activating characteristics of Staphylococcal immune-evasion protein Sbi to develop a pro-vaccine approach that spontaneously coats antigens with C3 degradation products in a natural way. We show that Sbi rapidly triggers the alternative complement pathway through recruitment of complement regulators, forming a tripartite complex that acts as a competitive antagonist of factor H, resulting in enhanced complement consumption. These functional results are corroborated by the structure of this complement activating Sbi-III-IV:C3d:FHR-1 complex. Finally, we demonstrate that Sbi, fused with Mycobacterium tuberculosis antigen Ag85b, causes efficient opsonisation with C3 fragments, thereby enhancing the immune response significantly beyond that of Ag85b alone, providing proof of concept for our pro-vaccine approach.